Examining the Level of Convergence Among Self-Regulated Learning Microanalytic Processes, Achievement, and a Self-Report Questionnaire. (August 2015) - Cleary, Timothy J.; Callan, Gregory L.; Malatesta, Jaime; Adams, Tanya
This study examined the convergent and predictive validity of self-regulated learning (SRL) microanalytic measures. Specifically, theoretically based relations among a set of self-reflection processes, self-efficacy, and achievement were examined as was the level of convergence between a microanalytic strategy measure and a SRL self-report questionnaire targeting similar strategic behaviors. Using a sample of 49 college students, we found that SRL microanalytic self-reflection measures evidenced high inter-correlations and demonstrated medium to large relations with self-efficacy and achievement, respectively. Although non-significant relations were observed between a microanalytic strategy measure and a SRL self-report questionnaire, the microanalytic measure was shown to be a more robust predictor of future performance in the college course. Consideration for the types of scoring procedures used with microanalysis and the implications and limitations of our results are also discussed.